The experience of grandmothers in the care of the adolescent who consumes psychoactive substances - Andressa Hithomi Takahara; Sueli Aparecida Frari Galera; Ana Carolina Guidorizzi Zanetti; Angélica Martins de Souza Gonçalves; Simone Terezinha Protti-Zanatta; Sonia Regina Zerbetto (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To apprehend the experience of grandmothers who take care of their grandchildren who consume psychoactive substances. Methods: A descriptive study with a qualitative approach conducted with five grandmothers of two health services in a city in the interior of São Paulo. Data have collected from July 2015 to May 2016, through semi-structured interviews and analyzed using the technique of thematic content analysis. Results: The grandmothers recognized that their grandchildren used drugs when they changed their behavior, which required them to take on the role of counselor and educator. The aging process and financial difficulty consisted in limits to care. Conclusion and implications for practice: The grandmothers suffered psychosocial, structural, and organizational impacts, requiring nurses to enhance their facilitator skills in relational processes between two distinct generations of age and values.